A Fuzzy Areal Assessment Approach for Potentially Contaminated Sites - Özdamar, Linet; Demirhan, Melek; Özpınar, Alper; KILANÇ, BURAK (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2000)
This article describes a new fuzzy areal site assessment approach in the detection of contaminated zones within a site which is under environmental investigation. Conventional techniques utilized in this held are mostly interpolation based. These methods interpolate the contaminant concentration values at unobserved locations using observed values. Unlike these interpolation techniques, the motivation of the approach introduced here consists of partitioning a given site into smaller sections. Partitioning is carried out iteratively where subregions of interest are divided into further smaller regions. This re-partitioning scheme leads to a dynamic grouping of observations, since areas of differing sizes and boundaries contain different sets of samples. The potential of an area to contain contaminated zones is assessed by a fuzzy measure which converts the data values in that area into an aggregate grade normalized on [0, 1]. Thus, this approach does not assume concentration values at unobserved locations, rather, an areal potential is evaluated.
Keywords: environmental site characterization; contaminated zones; fuzzy measures; adaptive partitioning algorithms; variograms; çevresel sitesi karakterizasyonu; kirlenmiş bölgeleri; bulanık önlemler; adaptif bölümleme algoritmaları; variogramlar